An analytic hierarchy process model to evaluate road section design - Barić, Danijela; Pilko, Hrvoje; Strujić, Josip (Transport, 2016)
The traffic system is as essential to modern society as the circulatory system to the human body. Road section design is therefore a key infrastructure activity for economic development, and multi-criteria decision-making can provide an interdisciplinary approach that moves beyond purely economic optimisation to include technological, technical and ecological factors. The present work describes applying the multi-criteria Analytical Hierarchy Process (AHP) method to evaluate road section design in an urban environment through differential weighting of various criteria and sub-criteria. The model is tested on a stretch of National Road D8 in the municipality of Podstrana near the city of Split (Croatia), which serves as an important route for commuters and tourists. The proposed AHP model provided reliable results that were robust to sensitivity analysis. This approach involving differential criterion weighting may prove useful for evaluating and selecting appropriate road section designs for this and other contexts.First published online: 30 Mar 2016